Near-Infrared Hemicyanine Fluorophores with Optically Tunable Groups: A ‘Leap Forward’ for in Vivo Sensing and Imaging - Huang, Jing; He, Long; Wang, Jiaoliang; Xu, Junchao; Yuan, Lin (Synlett, 2023)
Hemicyanine dyes, with a tunable optical site and high wavelength tailorability, are of significant importance in the fields of sensing and diagnosis. Following the discovery of the near-infrared (NIR) (650–900 nm) fluorescent dyes Changsha (CS) and Huda (HD) by our group, remarkable progress has been made in the development of hemicyanine-based probes for in vivo imaging and detecting. In this review, we summarize the key contributions made by our group in developing long-wavelength (650–1700 nm) hemicyanines and utilizing them to construct functional probes. Finally, potential drawbacks and future prospects of hemicyanine dyes/probes are discussed.1 Introduction2 Changsha (CS) Dyes3 Huda (HD) Dyes4 Construction of Hemicyanine Fluorophores in the NIR-II Region5 Summary and Outlook
Keywords: near-infrared; fluorophore; hemicyanine; molecular probe; fluorescence imaging